Performance Measurement of Academic Information Systems using Performance Prism and ISO/IEC 25010 - Liulliyah Liulliyah; Apol Pribadi Subriadi (Bina Nusantara University, 2020)
The aim of the research was to measure system performance information in terms of system quality using the ISO/IEC 25010 model and involve stakeholders using the Performance Prism (PP) model. The research applied an action research approach where researchers developed performance measurement models and solved existing problems. The research produced 41 performance indicators, which were used to measure academic information system. The results in general academic information systems have a performance value of 5,522.